تطبيق تعليم ترجمة وعلاقته بتعليم حفظ القرآن وفهمه (دراسة الحالة بمعهد حفظ القرآن مصباح النور جيماحي- إندونيسيا): Application of Teaching Translation and its Relationship to Teaching Memorize Qur’an (Case study at Ma’had Tahfidzul Qur’an Misbahul-nur Cimahi - Indonesia) - Wangsadanureja, Miftah (SIBAWAYH Arabic Language and Education, 2020)
The language of the Qur’an is Arabic. as the word of Allah subhanahu wataala: "And we sent down the Qur’an with Arabic" (Taha 20: 113). Therefore, the teaching of memorizing the Qur'an is closely related to students' understanding of Arabic. The way to do this for students who memorize the Qur’an, must use appropriate learning methods. One of them is learning the translation of the Qur’an. The purpose of this study, to determine the application of teaching translation of the Qur'an in improving the memorization of the Qur’an for students. Ma'had "Misbahul Nur" Cimahi Indonesia has been serving students in memorizing the Qur'an since 2010. Ma'had "Misbahul Nur" has used the translation method of memorizing the Qur'an in teaching memorizing the Qur'an. The approach used is a qualitative approach of a case study strategy, that descriptive research method is a method of finding a group of people, an object, a group of countries, and ways of thinking or one of the events in the present. The purpose of quality research is to provide a clear picture of the methodology who are realistic, accurate about the facts, and related to the research problem. From this research it's known that the application of teaching  translation of the Qur'an does not conflict with the teaching  memorize of the Qur'an even very helpful for memorizing the Qur'an. This can be seen from the results of students memorizing the Quran which shows an increase. Besides that it also helps students to understand the vocabulary contained in the Qur'an. Therefore, there is a relationship between teaching the translation of the Qur'an and teaching to memorize the Qur'an in order to understand students about the Qur'an in terms of meaning and content, especially at the ma'had Tahfidzul Qur'an, Misbahul Nur, who has used this method.